PELATIHAN, PENGEMBANGAN KARIR, DAN PRODUKTIVITAS KERJA KARYAWAN PT. WORLD INNOVATIVE TELECOMMUNICATION (MOTIVASI, 2023)
Purpose – This study aims to determine the effect of training and career development on employee productivity at PT. World Innovative Telecommunication, to determine the effect of training on the work productivity of OPPO promoter employees at PT. World Innovative Telecommunication, to determine the effect of career development on employee work productivity at PT. World Innovative Telecommunication simultaneously and partially. The type of research used is associative quantitative Design/methodology –The population in this study were all promoter employees at PT. World Innovative Telecommunication totaling 112 employees and the samples taken in this study were 53 respondents using the Simple Random Sampling sampling technique. The data used in this study are primary and secondary data. Data collection methods used through interviews and questionnaires or questionnaires. The analytical method used is qualitative which is then quantified. The data analysis technique used in this study is multiple linear regression analysis, F test, T test and the coefficient of determination. Findings - The results showed that there was a significant effect of training and career development on the work productivity of PT.World Innovative Telecommunication employees, there was a significant effect of training on the work productivity of PT.World Innovative Telecommunication employees and there was a significant effect of career development on the work productivity of PT.World Innovative Telecommunication employees.